Gaya Bahasa Kiasan pada Puisi Cara Menikmati Kenangan dengan Baik Karya Rieki Diah Pitaloka dan Agus Noor - Mutia Aksari; Arya Miza Amin; Ifa Suryani; Sarinah Rani (UIR Press, 2023)
This study examines the Analysis of Figurative Language Style in the Poetry of How to Enjoy Memories Well by Rieki Diah Pitaloka and Agus Noor. The purpose of this study was to determine the figurative language style of the poem Cara Menikmati Kenangan dengan Baik by Rieki Diah Pitaloka and Agus Noor. The data collection technique used in this study is the listening and note-taking technique. The approach used in this research is a qualitative research approach. The data analysis technique used is content analysis data analysis technique. Based on the results of the analysis, there are data that can be classified based on the meaning of figurative language style in Keraf theory which describes the types of language styles into various types.